2020
DOI: 10.1038/s41598-020-78530-9
|View full text |Cite
|
Sign up to set email alerts
|

ATP-binding cassette transporter 13 mRNA expression level in schizophrenia patients

Abstract: The objective of this study was to investigate the expression and clinical role of ATP-binding cassette transporter 13 (ABCA13) gene previously shown to be associated with schizophrenia (SZ) through Genome-wide association studies studies. Thirty-two first-episode drug-naive SZ patients and forty-eight age and gender-matched healthy controls were enrolled in this study. We measured ABCA13 mRNA expression levels using quantitative real-time PCR at baseline and 12 weeks after antipsychotic therapy. Moreover, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(28 reference statements)
0
1
0
Order By: Relevance
“… 67 Furthermore, two studies showed enhanced ABCA13 mRNA expression in schizophrenic patients after different antipsychotic treatments, suggesting a role of this transporter in psychiatric disorders. 48 , 65 , 66 However, no association between ABCA13 and AD has been found.…”
Section: Part I: Status Quomentioning
confidence: 98%
“… 67 Furthermore, two studies showed enhanced ABCA13 mRNA expression in schizophrenic patients after different antipsychotic treatments, suggesting a role of this transporter in psychiatric disorders. 48 , 65 , 66 However, no association between ABCA13 and AD has been found.…”
Section: Part I: Status Quomentioning
confidence: 98%